Associations between low body mass index and mortality in patients with sepsis: A retrospective analysis of a cohort study in Japan. - Tetsuya Sato; Daisuke Kudo; Shigeki Kushimoto; Masatsugu Hasegawa; Fumihito Ito; Sathoshi Yamanouchi; Hiroyuki Honda; Kohkichi Andoh; Hajime Furukawa; Yasuo Yamada; Yuta Tsujimoto; Manabu Okuyama; et al. (PLoS ONE)
Background The distribution of body mass in populations of Western countries differs from that of populations of East Asian countries. In East Asian countries, fewer people have a high body mass index than those in Western countries. In Japan, the country with the highest number of older adults worldwide, many people have a low body mass index. Therefore, this study aimed to determine the association between a low body mass index and mortality in patients with sepsis in Japan. Methods We conducted this retrospective analysis of 548 patients with severe sepsis from a multicenter prospective observational study. Multivariate logistic regression analyses determined the association between body mass index and 28-day mortality adjusted for age, sex, pre-existing conditions, the occurrence of septic shock, Acute Physiology and Chronic Health Evaluation II scores, and Sequential Organ Failure Assessment scores. Furthermore, the association between a low body mass index and 28-day mortality was analyzed. Results The low body mass index group represented 18.8% of the study population (103/548); the normal body mass index group, 57.3% (314/548); and the high body mass index group, 23.9% (131/548), with the 28-day mortality rates being 21.4% (22/103), 11.2% (35/314), and 14.5% (19/131), respectively. In the low body mass index group, the crude and adjusted odds ratios (95% confidence intervals) for 28-day mortality relative to the non-low body mass index (normal and high body mass index groups combined) group were 2.0 (1.1-3.4) and 2.3 (1.2-4.2), respectively. Conclusion A low body mass index was found to be associated with a higher 28-day mortality than the non-low body mass index in patients with sepsis in Japan. Given that older adults often have a low body mass index, these patients should be monitored closely to reduce the occurrence of negative outcomes.